Identification and influence factors analysis of blade crack mistuning in hard-coated blisk based on modified component mode mistuning reduced-order model. Issue 3 (September 2021) - Xu, Kunpeng; Yan, Xianfei; Du, Dongxu; Sun, Wei
Blade crack will cause severe mistuning of hard-coated blisks, which will lead to vibration localization. To identify crack mistuning and analyze influence factors, in this study, a mistuning identification method of blade cracks in hard-coated blisks is presented based on modified component mode mistuning reduced-order model, in which the hard-coated blisk with blade crack is decomposed into a substructure of tuned hard-coated blisk and a substructure of coated blade with cracks. Crack mistuning of each coated blade can be obtained by a single identification calculation. After verifying the rationality of this identification method, the influence factors of blade crack mistuning are analyzed. The influence factors include the crack location on the coated blade (cracks occurring only in coating or only in blade substrate or both in blade substrate and coating), crack length, crack position in the radial direction of the blisk, and modal data type of coated blisk used for mistuning identification calculation. The research results show that, with the increase of crack length, the mistuning of crack occurring only in the coating does not increase continuously but decreases firstly and then increases. For the first bending modes, the closer the blade crack is to the blade root, the larger the mistuning is. For the second bending modes, the blade crack located at the position of maximum modal displacement will produce large mistuning. For hard-coated blisk with blade crack, these crack mistuning variation rules are of great significance to the dynamic analysis and the determination of the crack location.